Kosovo- Serbia Agreements between Creative and Destructive Ambiguity - Bardhok Bashota; Bujar Dugolli (Revista UNISCI, 2019)
The European Union (EU) engagement through a pro-active approach in facilitating the negotiation process for normalization of Kosovo-Serbia relations is the most complex and challenging motion ever undertaken within the European External Action Service (EEAS). Since the process aimed to resolve the protracted disputes between the parties, efficient management of this process required the application of a specific approach. This article examines how the 'creative ambiguity' became the key approach to reaching the 2013 Agreement for Normalization of Relations between two countries, which foresaw the creation of a so-called Association of Serb Majority Municipalities. It concludes that the inertia of the process for normalization of relations between the engaged parties urged them to reach a comprehensive agreement, even with the possibility of a land swap.